Modulation of PC1/3 activity by a rare double-site homozygous mutation - Ni, Yanyan; Chen, Xiangxiang; Sun, Yi; Pan, Jiarong; Tang, Chao; Yuan, Tianming (Frontiers in Pediatrics, 2022)
Objectives: Preprotein convertase 1/3 deficiency is a rare autosomal recessive disorder in which patients present with malabsorptive diarrhea and a series of symptoms of endocrine disorders such as polydipsia, reactive hypoglycemia, growth hormone deficiency, hypothyroidism, adrenal insufficiency, and early onset obesity. In its essence, pituitary hormone deficiency is caused by insufficient cleavage of pituitary prohormones. Here, we describe a female child with a rare double-site homozygous mutation in PCSK1 (Proprotein convertase subtilisin/kexin-type 1) gene, and thereby intend to investigate the relationship between these novel mutation sites and changes in protein synthesis and function. Methods: We tested this patient's blood and urine fecal indicators of infection, blood electrolytes, and relevant endocrine hormone levels in the laboratory. Next Generation Sequencing was applied to screen the patient’s DNA. Western Blot was performed to evaluate the mutant protein’s expression. The enzymatic activity was measured as the rate of cleavage of a synthetic fluorogenic substrate in a specific solution. Results: We found that this patient presented shortly after birth with uncorrectable diarrhea and symptoms of metabolic acidosis with hypothyroidism. Next Generation Sequencing revealed that a rare double-site homozygous missense mutation, c.763G>A (p.G255R) and c.758C>T (p.S253L), were detected in exon 7 of PCSK1 (Proprotein convertase subtilisin/kexin-type 1) gene on chromosome 5 of the patient. Western blotting revealed that there was no significant decrease in protein synthesis levels in the mutant phenotype compared to the wild type. Compared with WT type, the proteins expressed by the mutations showed a significant decrease in the enzyme activity towards the fluorescent substrates. However, neither the single site mutation p.S253L or p.G255R, nor the double-site mutation of both, all showed no significant differences from each other. Conclusions: These two missense mutations have not been reported before, and it is even rarer to find homozygous variation of two sites in one patient. This study identifies two novel mutations for the first time and further investigates the changes in protein synthesis and enzyme activity, providing a new pathway to continue to explore the pathogenesis of diseases associated with the function of PC1/3.